2014
DOI: 10.7717/peerj.425
|View full text |Cite
|
Sign up to set email alerts
|

FOCUS: an alignment-free model to identify organisms in metagenomes using non-negative least squares

Abstract: One of the major goals in metagenomics is to identify the organisms present in a microbial community from unannotated shotgun sequencing reads. Taxonomic profiling has valuable applications in biological and medical research, including disease diagnostics. Most currently available approaches do not scale well with increasing data volumes, which is important because both the number and lengths of the reads provided by sequencing platforms keep increasing. Here we introduce FOCUS, an agile composition based appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 28 publications
0
75
0
Order By: Relevance
“…Members of the community submitted results for ten taxonomic profilers to the CAMI challenge: CLARK 32 ; ‘Common kmers’ (an early version of MetaPalette 33 , abbreviated CK in the figures); DUDes 34 ; FOCUS 35 ; MetaPhlAn 2.0 36 ; Metaphyler 37 ; mOTU 38 ; a combination of Quikr 39 , ARK 40 , and SEK 41 (abbreviated Quikr); Taxy-Pro 42 ; and TIPP 43 . For several programs, results were submitted with multiple versions or different parameter settings, bringing the number of unique submissions to twenty.…”
Section: Resultsmentioning
confidence: 99%
“…Members of the community submitted results for ten taxonomic profilers to the CAMI challenge: CLARK 32 ; ‘Common kmers’ (an early version of MetaPalette 33 , abbreviated CK in the figures); DUDes 34 ; FOCUS 35 ; MetaPhlAn 2.0 36 ; Metaphyler 37 ; mOTU 38 ; a combination of Quikr 39 , ARK 40 , and SEK 41 (abbreviated Quikr); Taxy-Pro 42 ; and TIPP 43 . For several programs, results were submitted with multiple versions or different parameter settings, bringing the number of unique submissions to twenty.…”
Section: Resultsmentioning
confidence: 99%
“…Given the variety of use-cases, it is important to understand the benefits and drawbacks of the particular taxonomic profiler for different applications. While there has been much effort in developing taxonomic profiling methods [1][2][3][4][5][6][7][8][9][10][11][12], only recently have community efforts arisen to perform unbiased comparisons of such techniques and assess their strengths and weaknesses [13,14]. Critical obstacles to such comparisons have been a lack of consensus on performance metrics and output formats by the community, as different taxonomic profilers report their results in a variety of formats and interested parties had to implement their own metrics for comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews have indicated that significant challenges exist for each of these tasks, and in particular taxonomic profiling methods still struggle to accurately characterize metagenomic samples below the genus taxonomic level [17,15]. Many of these taxonomic profiling tools attempt to determine the fewest taxa required to explain some measurement of a given metagenomic sample [4,16,18,11]. In our previous work [12,13], we introduced such a method that leverages compressive sensing techniques to find the fewest taxa that fits the frequency of short sequences of nucleotides (i.e., k-mers) in a given sample.…”
Section: Introductionmentioning
confidence: 99%